Analisis Wacana Pada Lirik Lagu “Life Goes On” Karya Boy Group BTS - Puteri, Fransisca Nirmala Gunawan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Korean Pop (Kpop) is a type of modern alternative music genre originating from South Korea. Kpop is actually aproduct of Hallyu (Korean wave) which is also integrated with other Hallyu products such as films, food, fashionand other Korean culture. Kpop culture actors are synonymous with a group of people formed in a group (boygroup or girl group) who sing while performing modern dance choreography. Beyond The Scene or BangtanSeonyeondan (BTS) is one of the boy groups that is very popular at the moment. This research analyzes thediscourse in one of the lyrics of the Boy Group BTS song, entitled